(Ba1−xNax)F(Zn1−xMnx)Sb: A novel fluoride-antimonide magnetic semiconductor with decoupled charge and spin doping. (1st November 2022) - Zhao, Xueqin; Dong, Jinou; Fu, Licheng; Gu, Yilun; Zhang, Rufei; Yang, Qiaolin; Xie, Lingfeng; Tang, Yinsong; Ning, Fanlong
Abstract: We report the successful synthesis and characterization of a novel 1111-type magnetic semiconductor (Ba1− x Na x )F(Zn1− x Mn x )Sb (0.05 ≤ x ≤ 0.175) with tetragonal ZrSiCuAs-type structure, which is isostructural to the layered iron-based superconductor La(O, F)FeAs. Na substitutions for Ba and Mn substitutions for Zn introduce carriers and local magnetic moments, respectively. Ferromagnetic interaction is formed when Na and Mn are codoped, demonstrating that local magnetic moments are mediated by carriers. Iso-thermal magnetization shows that the coercive field is as large as 12 000 Oe, which is also reflected in the large split between the temperature-dependent magnetization in zero-field-cooling and field-cooling condition. AC susceptibility under zero field demonstrates that samples evolve into spin-glass state below spin freezing temperature T f . The measurements of temperature-dependent resistivity indicate that (Ba1− x Na x )F(Zn1− x Mn x )Sb exhibits semiconducting behaviour.